ANALISIS PENGEMBANGAN ELECTRONIC GOVERNMENT DI DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI JAWA TENGAH (Studi pada Website, Lumbung Data, Bio Sistem Online, dan Jateng Pintar, Berdasarkan Intruksi Presiden Nomor 3 Tahun 2003) - Ridhayanti Annisa Puspa; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Electronic Government is the implementation of the use of information technology in government services to the public. Department of Education and Culture of Central Java as the institution of public service providers in the field of education began to build Electronic Government system since 2011. The existence of limited resources supporting the development of Electronic Government itself less than the maximum. The approach used is descriptive qualitative with data collection technique through interview, observation, and documentation. To assess the development of Electronic Government in the Department of Education and Culture of Central Java, used the level of development of Electronic Government starting from level 1 preparation, level 2 maturation, level 3 consolidation and level 4 utilization. In addition, to know the supporting and inhibiting factors using the successful elements of Electronic Government development support, capacity, and values. The results showed that the development of Electronic Government in the Department of Education and Culture of Central Java Province is at level 2 maturation. The development of the Electronic Government in the Department of Education and Culture of Central Java has not reached the level of 3 consolidation due to inhibiting factors of inadequate application infrastructure, the absence of Electronic Government related regulations at the service level, overlapping duties and obligations of employees, and the minimum budget of Electronic Government development. While the supporting factor is cooperation between government and private parties, the UPT Office that helps the implementation of tasks in the field of ICT, as well as training conducted regularly for employees. It is suggested to the Department of Education and Culture of Central Java to add more diverse application infrastructure, increase employees to avoid overlap, improve socialization to the public regarding Electronic Government concept, and improve financial management.